2015
DOI: 10.1103/physrevstper.11.020135
|View full text |Cite
|
Sign up to set email alerts
|

Student ability to distinguish between superposition states and mixed states in quantum mechanics

Abstract: Superposition gives rise to the probabilistic nature of quantum mechanics and is therefore one of the concepts at the heart of quantum mechanics. Although we have found that many students can successfully use the idea of superposition to calculate the probabilities of different measurement outcomes, they are often unable to identify the experimental implications of a superposition state. In particular, they fail to recognize how a superposition state and a mixed state (sometimes called a "lack of knowledge" st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…They also did not take into account the phase shifts of each photon path component and how the phase difference between the U and L paths causes constructive and destructive interference of single photons at the detectors. Students' conceptual difficulties involving superposition states in quantum mechanics has been found in other contexts as well [7].…”
Section: Students' Conceptual Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They also did not take into account the phase shifts of each photon path component and how the phase difference between the U and L paths causes constructive and destructive interference of single photons at the detectors. Students' conceptual difficulties involving superposition states in quantum mechanics has been found in other contexts as well [7].…”
Section: Students' Conceptual Difficultiesmentioning
confidence: 99%
“…[1][2][3][4][5][6]), and focused on diverse pedagogical approaches for helping students learn quantum mechanics better (see, e.g., Refs. [7][8][9][10][11][12][13][14]). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, relative phase and various setups of the Stern-Gerlach experiment are taught extensively in the sophomore-level quantum mechanics course. The task was inspired by questions used by Passante et al to probe student ability to distinguish superposition states from mixed states [21].…”
Section: Observational Experiment: Studymentioning
confidence: 99%
“…The results showed that many students confuse Hilbert space with physical space and have difficulty reasoning about what components of spin need to be measured. Passante et al [21] probed whether or not students recognize that position states and mixed states are different experimentally, as well as the reasoning that students used to justify their answers. They found that many students do not recognize that superposition states and mixed states are experimentally distinguishable.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum mechanics (QM) is a particularly challenging subject for upper-level undergraduate and graduate students in physics [1][2][3][4]. Guided by research studies conducted to identify student difficulties with QM and findings of cognitive research, we have been developing a set of researchbased learning tools including the Quantum Interactive Learning Tutorials (QuILTs) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%